Deviations from Purchasing Power Parity in the Long Run - ADLER, MICHAEL; LEHMANN, BRUCE (Journal of Finance, 1983)
ABSTRACT This paper demonstrates that deviations from purchasing power parity reveal a remarkable and possibly startling consistency with martingale behavior during both fixed and flexible rate periods, for a wide variety of countries, and in both monthly and annual data. Since this pattern appears to be much more general than one would expect on the basis of models founded on international commodity arbitrage, the paper proposes an alternative explanation which instead relies on financial arbitrage in bonds as the underlying mechanism.